Fast growth of self-aligned titania nanotube arrays with excellent transient photoelectric responses. (1st September 2016) - Cao, Chunbin; Zhang, Guoshun; Ye, Jian; Hua, Rimao; Sun, Zhaoqi; Cui, Jingbiao
Abstract: Self-aligned titania nanotube arrays (TNAs) were fabricated by electrochemical anodization at high voltage of 120 V in an electrolyte containing high F − concentration. Compared to the TNAs obtained by traditional anodic conditions, the resulted samples show more uniform surface, firmer structure, and stronger adhesion to the Ti substrate. Importantly, the anodization time can be greatly reduced from several hours to tens of seconds. The photoelectric current density produced by the new TNAs is 1.94 times higher than that of TNAs prepared under traditional conditions. A new growth mechanism involving columnar oxide etch (COE) model is proposed to explain the inner evolution of the TNAs. The effect of anodic current oscillations on the formation of nanotube, tube ridge, and porous structures are investigated. This ultrafast growth of TNAs will have significant impact on large-scale device applications.